Toward a Better Understanding of Brain Lesions during Metachromatic Leukodystrophy Evolution - Martin, A. (AJNR Am J Neuroradiol, 2012)
BACKGROUND AND PURPOSE: The prospect of new therapies in MLD stresses the need to refine the indications for treatment. The aim of this study was, therefore, to perform a detailed analysis of MRI brain lesions at diagnosis and follow-up, to better understand the natural history of MLD. MATERIAL AND METHODS: This retrospective case-control study (2005–2010) looked at 13 patients with MLD (2–5 years of age) with 28 MRIs (mean follow-up, 2 years), compared with 39 age- and sex-matched controls. All MRIs were evaluated qualitatively and semiquantitatively. The Student t test, Wilcoxon signed rank test, and Pearson correlation were used for statistical analysis (P < .05). RESULTS: In addition to diffuse symmetric supratentorial WM T2 hyperintensities with a tigroid pattern (70%) and T2 hyperintensities in the CC (100%) and internal capsules (46%), we found significant GM abnormalities such as thalamic T2 hypointensity (92%), thalamic (23%, P < .05, EJ) and caudate nuclei (23%, P < .05, EJ) atrophy, and cerebellar atrophy without WM involvement (15%). The pattern of splenium involvement progression was misleading, with initially diffuse high signal intensity, which later became curvilinear before finally progressing to atrophy (23%, P < .05; EJ). This should not be mistaken for a disease regression. Spectroscopy confirmed a decrease in the NAA/Cr ratio, an increase in the Cho/Cr ratio and in myo-inositol, and a lactate resonance. CONCLUSIONS: Thalamic changes may be a common finding in MLD, raising the prospect of primary GM lesions. This may prove important when evaluating the efficacy of new treatments.